The S. cerevisiae SET3 complex includes two histone deacetylases, Hos2 and Hst1, and is a meiotic-specific repressor of the sporulation gene program - Pijnappel, W.W.M. Pim (Cold Spring Harbor Laboratory Press, 2001)
Set3 is one of two proteins in the yeast Saccharomyces cerevisiae that, like Drosophila Trithorax, contains both SET and PHD domains. We found that Set3 forms a single complex, Set3C, with Snt1, YIL112w, Sif2, Cpr1, and two putative histone deacetylases, Hos2 and NAD-dependent Hst1. Set3C includes NAD-dependent and independent deacetylase activities when assayed in vitro. Homology searches suggest that Set3C is the yeast analog of the mammalian HDAC3/SMRT complex. Set3C represses genes in early/middle of the yeast sporulation program, including the key meiotic regulators ime2 and ndt80. Whereas Hos2 is only found in Set3C, Hst1 is also present in a complex with Sum1, supporting previous characterizations of Hst1 and Sum1 as repressors of middle sporulation genes during vegetative growth. However, Hst1 is not required for meiotic repression by Set3C, thus implying that Set3C (−Hst1) and not Hst1–Sum1, is the meiotic-specific repressor of early/middle sporulation genes.